2020
DOI: 10.1108/aaaj-05-2020-4556
|View full text |Cite
|
Sign up to set email alerts
|

Advancing research into accounting and the UN Sustainable Development Goals

Abstract: PurposeThis paper introduces a special section devoted to accounting scholarship that addresses the United Nations (UN) Sustainable Development Goals (SDGs) and has three purposes. First, to explore the puzzle of a relative absence of accounting-related scholarship that addresses the SDGs. Second, the papers within the special section are introduced and located within streams of existing research and practice. Third, the paper then suggests framings, approaches and/or conditions under which the authors might s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 35 publications
(66 reference statements)
1
106
0
1
Order By: Relevance
“…Although many academics agree with the strategic role covered by HEIs within society (Gusmão Caiado et al 2018;Moggi 2019), the multidimensional character of the SDGs underlines the need to conduct specific reflections on them. Prior studies highlighted that the contribution made by any type of organization to Agenda 2030 is limited by the coexistence of positive, negative, and neutral interlinkages between the 17 SDGs (Bebbington and Unerman 2020;Nilsson et al 2016). In this sense, even with the presence of a willingness to contribute to all the SDGs, specific goals will be prioritized more than others (Avrampou et al 2019;Pizzi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although many academics agree with the strategic role covered by HEIs within society (Gusmão Caiado et al 2018;Moggi 2019), the multidimensional character of the SDGs underlines the need to conduct specific reflections on them. Prior studies highlighted that the contribution made by any type of organization to Agenda 2030 is limited by the coexistence of positive, negative, and neutral interlinkages between the 17 SDGs (Bebbington and Unerman 2020;Nilsson et al 2016). In this sense, even with the presence of a willingness to contribute to all the SDGs, specific goals will be prioritized more than others (Avrampou et al 2019;Pizzi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interconnectedness among indicators and disaggregation of accounting data are factors that can lead to an inaccurate evaluation. The elaboration of instruments inspired on the 2030 Agenda and harmonized to accounting standards is highly necessary as stated by Bebbington and Unerman (2020). The core business of companies may be a font of subjectivity when deciding actions toward the SDGs.…”
Section: Discussionmentioning
confidence: 99%
“…To do this required organizations to undertake sustainability accounting in order to manage their environmental and social impacts, identify targets and then report them [38]. Six years after their earlier paper, Bebbington and Unerman [39] (p. 1659) observed that although the SDGs had received much attention from some academic disciplines, there was substantially less from the academic accounting community explaining that "to do so is not straightforward." This was confirmed in research into 153 Italian public interest entities by Pizzi, Rosati and Venturelli [40], which supported the findings by Oxfam [41] that 'walking' and 'talking' about SDGs are not fully achieved, and there is only limited disclosure around the SDGs.…”
Section: The Un's Sustainable Development Goals and Corporate Reportingmentioning
confidence: 99%